Perception of ability-motivation-opportunity oriented HRM practices and organizational commitment: The role of task uncertainty - Michał Ujma, Business Manager; Tomasz Ingram (Journal of Entrepreneurship, Management and Innovation)
Using the premises of the Ability-Motivation-Opportunity theory, the main aim of the paper is to answer the question of how HRM practices affect individual commitment considering task uncertainty as for the important moderator of the relationships between HRM practices and commitment. For that purpose, we use data from 164 employees working in 32 teams in international recruitment and selection agency departments located in Poland. We find out that HR practices differently affect organizational commitment. In particular, HR practices focused on fostering employees’ motivation and creating opportunities within organizations positively influence affective commitment, while HR practices focused on fostering employees’ abilities are negatively related to continuance commitment. Further, we also find that task uncertainty significantly moderates the relationship between HR practices and continuance commitment. The study finishes with theoretical and practical implications and future research directions.